World first for zero liquid discharge. Issue 1 (January 2016) - Unknown
Abstract : In China, power generation growth has driven power plant wastewater regulations to the level of zero liquid discharge. The Huaneng Group's new treatment plant debuts the world's first commercial application of forward osmosis-based zero liquid discharge.